Effectiveness of Cefazolin Prophylaxis on the Growth of Postoperative Bacterial Colony: Study on Grade I and Grade II Open Fracture Patients at Saiful Anwar General Hospital - Rasyidin Rumlus; Fahmi Dimas Abdul Aziz; Umi Fatmawati (LPPM Universitas Abdurrab, 2025)
ABSTRACT The use of prophylactic antibiotics prior to surgery has been shown to reduce the incidence of post-operative infections. Prophylactic antibiotics are recommended only for procedures with a high incidence of infection and procedures with very serious consequences of infection. Open fractures are a very serious infection. This study aims to determine the effectiveness of cefazolin prophylaxis on bacterial colony growth 24 hours post-operatively. This study used a prospective observational cohort method conducted at Dr. Saiful Anwar General Hospital in Malang from Agustus to December 2024, and total sampling was used for sample collection. The effectiveness of cefazolin was assessed based on the growth of bacterial colonies and bacterial sensitivity to antibiotics. The results of wound culture examinations in 30 subjects with grade I and grade II wounds showed 43 positive bacterial colonies, namely coagulase-negative Staphylococcus, out of a total of 43 bacterial colonies that grew, reaching a sensitivity of 100% at 24 hours postoperatively. The use of cefazolin prophylaxis was effective in reducing bacterial colony growth 24 hours postoperatively. Keywords: Cefazolin, open fractures, prophylaxis antibiotic